L-Plastin promotes podosome longevity and supports macrophage motility. (October 2016) - Zhou, Julie Y.; Szasz, Taylor P.; Stewart-Hutchinson, Phillip J.; Sivapalan, Janardan; Todd, Elizabeth M.; Deady, Lauren E.; Cooper, John A.; Onken, Michael D.; Morley, S. Celeste
Highlights: Podosome duration is reduced in the absence ofl -plastin. Resident peritoneal macrophages froml -plastin −/− mice do not polarize. Efficient migration of resident peritoneal macrophages requiresl -plastin. Abstract: Elucidating the molecular regulation of macrophage migration is essential for understanding the pathophysiology of multiple human diseases, including host responses to infection and autoimmune disorders. Macrophage migration is supported by dynamic rearrangements of the actin cytoskeleton, with formation of actin-based structures such as podosomes and lamellipodia. Here we provide novel insights into the function of the actin-bundling proteinl -plastin (LPL) in primary macrophages. We found that podosome stability is disrupted in primary resident peritoneal macrophages from LPL −/− mice. Live-cell imaging of F-actin using resident peritoneal macrophages from LifeACT-RFP + mice demonstrated that loss of LPL led to decreased longevity of podosomes, without reducing the number of podosomes initiated. Additionally, macrophages from LPL −/− mice failed to elongate in response to chemotactic stimulation. These deficiencies in podosome stabilization and in macrophage elongation correlated with impaired macrophage transmigration in culture and decreased monocyte migration into murine peritoneum. Thus, we have identified a role for LPL in stabilizing long-lived podosomes and in enabling macrophage motility.